MODEL STRATEGI COPING ANAK USIA DINI DI PANTI ASUHAN KOTA MALANG - sarah emmanuel haryono; mochammad ramli akbar (Pedagogi : Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 2016)
This  study  aimed  to  describe  the  model  of  coping  strategies  applied  in  the orphanage.  This  study  uses  a  qualitative  case  study,  and  using  model  analysis  techniques Miles  &  Hubberman.  The  research  was  done  at  King  Kids  orphanage  at,  Malang  City. Based  on  research  conducted,  the  model  for  coping  strategies  that  are  applied  to  early childhood at the orphanage is problem focused coping and emotional focused coping with learning  coping  strategies  for  early  childhood  in  the  orphanage  is  to  use  (1)  the  problem focused  coping  &  emotional  focused  coping  by  (a  )  sets  strict  rules  on  the  environment orphanage,  (b)  verbal  approach  to  the  child  repeatedly  and  continuously,  (c)  establish early childhood to be able to verbalize feelings and behavior in a discussion forum.  (2) The purpose  of  learning  coping  strategies  for  early  childhood  in  orphanages  are  (a)  to  be  able to cope  with  all  the  stress  experienced  and  (b)  capable  of  taking  a  life  outside  the orphanage.  Keywords:  orphanage, caregiver, coping strategies